2020
DOI: 10.1177/1759091420910933
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Involvement in Noradrenergic Regulation of Ventromedial Hypothalamic Nucleus Glucoregulatory Neurotransmitter and Stimulus-Specific Glycogen Phosphorylase Enzyme Isoform Expression

Abstract: Norepinephrine (NE) directly regulates ventromedial hypothalamic nucleus (VMN) glucoregulatory neurons and also controls glycogen-derived fuel provision to those cells. VMN nitric oxide (NO) and c-aminobutyric acid (GABA) neurons and astrocytes express estrogen receptor-alpha (ERa) and ER-beta (ERb) proteins. Current research used selective ERa (1,3Bis(4-hydroxyphenyl)-4-methyl-5-[4-(2-piperidinylethoxy)phenol]-1H-pyrazole dihydrochloride) or ERb (4-[2-phenyl-5,7bis(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-3-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…NE has well documented regulatory effects on astrocyte glycogen metabolism in vitro [41,42]. We found that NE inhibits VMN GS protein expression, and promotes divergent adjustments in AMP-sensitive glycogen phosphorylase (GP)-brain type (up-regulated by NE) versus NE-sensitive GP-muscle (down-regulated by NE) variant profiles via ERα or -β activity, respectively [35]. These data uniquely demonstrate ER-dependent NE control of VMN GP variant expression.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…NE has well documented regulatory effects on astrocyte glycogen metabolism in vitro [41,42]. We found that NE inhibits VMN GS protein expression, and promotes divergent adjustments in AMP-sensitive glycogen phosphorylase (GP)-brain type (up-regulated by NE) versus NE-sensitive GP-muscle (down-regulated by NE) variant profiles via ERα or -β activity, respectively [35]. These data uniquely demonstrate ER-dependent NE control of VMN GP variant expression.…”
mentioning
confidence: 69%
“…We conducted studies to address the premise that estradiol may modulate NO and/or GAD neuron receptivity to NE. Using pharmacological and high-resolution microdissection tools in a characterized OVX, plus an estradiol replacement model in which plasma estradiol levels are reinstated within the physiological range [32][33][34], we investigated whether VMN ERα and/or ERβ modulate NE control of nitrergic and GABAergic neuron AR and transmitter marker protein expression in the female rat [35]. The research plan involved a pretreatment by intra-VMN administration of MPP, PHTPP, or vehicle, prior to the injection of NE into the same location.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DVC NE governs hypoglycemic patterns of VMN AMPK activation and neurotransmitter marker protein expression [ 48 ]. Noradrenergic regulation of VMN glycogen metabolic enzyme protein expression was initially documented by studies that showed that exogenous NE inhibits GS protein expression but imposes divergent, e.g., stimulatory versus inhibitory, effects on AMP-sensitive GPbb and NE-sensitive GPmm profiles, respectively [ 49 ]. As VMN astrocytes obtained by laser-catapult microdissection express alpha 1 (α 1 ), alpha 2 - (α 2 ) and beta 1 - (β 1 ) adrenergic receptor (AR) proteins [ 50 ], it is reasonable to presume that the noradrenergic regulation of the GP variant expression involves, in part, direct input to these cells.…”
Section: Hindbrain Noradrenergic Regulation Of Vmn Glycogen Metabomentioning
confidence: 99%
“…VMN glycogen mass and/or turnover is a plausibly important metabolic variable that is subject to careful monitoring. As glycogen-derived substrate fuel stream has documented influence on VMN metabolic regulatory transmitter signaling, as indicated by evidence that NE causes 4CIN-reversible changes in the VMN nNOS and GAD protein expression [ 49 ], the astrocyte glycogen depot can be viewed as a plausible substrate for noradrenergic control of VMN gluco-regulatory function. There is need for consideration, however, whether glycogen-derived lactate affects VMN metabolic neurons as an energy fuel and/or signaling molecule [ 65 ].…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%